PENDIDIKAN HUMANIS JOHN DEWEY DALAM PERSPEKTIF PENDIDIKAN ISLAM - Mubarok, Ruma (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Education is a process toward birth humanizationhumanly valuable human being. The main agenda of education isthe process of humanizing humans being human. That process iscalled humanization; the human form becomes a true human being.Education as a process carried out by a community in order toprepare the next generation to be able to socialize and adapt to theculture they profess, actually one of the traditions of the human racethat is almost as old as mankind. Education had been since timeimmemorial is one form of human effort in order to maintain thecontinuity of the existence of life and their culture.